2022
DOI: 10.4103/njcp.njcp_1805_21
|View full text |Cite
|
Sign up to set email alerts
|

Can the Hydrogel Form of Sodium Ascorbate be Used to Reverse Compromised Resin Infiltrant Penetration After Bleaching?

Abstract: Aims: The aim of this study was to investigate the effects of an antioxidant on the bleaching-induced reduction in the penetration depth of infiltrant resins. Materials and Methods: White spot lesions (WSLs) were created on 105 bovine tooth samples, each measuring 6 × 4 × 4 mm. Five samples were randomly selected for the examination of lesion characteristics. The remaining 100 samples were then divided into four groups (n = 25). In Group I, the WSLs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…15 Furthermore, numerous studies have examined the efficacy of sodium ascorbate in removing oxygen radicals generated by bleaching gels from enamel and dentin. 37,38,57…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…15 Furthermore, numerous studies have examined the efficacy of sodium ascorbate in removing oxygen radicals generated by bleaching gels from enamel and dentin. 37,38,57…”
Section: Resultsmentioning
confidence: 99%
“…18 Over 20 studies have shown that a 10% SA concentration applied for regular application time (up to 10 min) is sufficient to neutralize the free oxygen present in enamel and dentin after bleaching and to restore the bond strength. 20,24,38 One study suggested that using antioxidant to neutralize the oxidizing effect of a bleaching agent requires at least one-third of the bleaching time to completely reverse its effect. 39 Another study found that a 15-min application of antioxidants was found to be adequate after three 15-min bleaching sessions, in line with our findings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, the vast majority stand behind the protective properties of resin infiltration. The overall success of the resin infiltration approach, including its masking effect, depends on the ability of the resin to infiltrate into porous spaces under an intact surface layer [ 18 ]. If cavitation has not occurred in the initial lesion, and the resin infiltration is performed as specified by the manufacturer, treatment will be successful.…”
Section: Discussionmentioning
confidence: 99%